Influence of milling time and binder composition on phase evolution in WC-based composite powders fabricated via high-energy ball milling - Aidarova, Madina; Kurbanbekov, Sherzod; Kizatov, Aibar; Urkunbay, Azamat; Bayatanova, Lyaila; Rutkowska-Gorczyca, Małgorzata; Amangeldiyeva, Yulduz (Frontiers in Materials, 2025)
Cobalt-free WC-(Fe/Ni) composite powders were evaluated as practical alternatives to WC-Co, with emphasis on how the post-milling powder state governs downstream processing. Blends of 88 wt% WC-12 wt% Fe, 88 wt% WC-12 wt% Ni, and 88 wt% WC-6 wt% Fe-6 wt% Ni were ball-milled for 0–4 h at 500 rpm in Ar. Phase constitution was assessed by X-ray diffraction; crystallite size and microstrain were quantified by Williamson-Hall/Scherrer; particle-size distributions (PSD) were measured by laser diffraction and benchmarked against SEM. Across all series, WC and metallic binder were retained while W2C/W remained at trace levels (<1%). In WC-FeNi, the free-Ni fraction decreased (1.9 → 0.5%) and Fe increased (9.5 → 23.6%), indicating formation of an Fe(Ni) solid solution during milling. WC crystallites refined from ∼50-55 nm to 22.6 nm (WC-Fe), 20.7 nm (WC-Ni), and 21.1 nm (WC-FeNi) by 4 h, with most refinement achieved within 0–2 h. In parallel, PSD shifted to larger particle sizes due to cold welding: D50 increased 3.40 → 10.30 µm (Fe), 2.87 → 7.27 µm (Ni), and 4.11 → 7.42 µm (FeNi), while PSD/SEM jointly evidenced multigrain aggregates in the 5–10 µm range. This establishes an inverse micro/nano linkage wherein agglomerates coarsen as WC crystallites refine. Among the chemistries, WC-FeNi at 1–2 h provided the most balanced outcome ∼21 nm crystallites, moderate microstrain, and limited D50 growth defining a preferred window for uniform compaction and sintering. These results clarify processing–structure relations in cobalt-free WC composites and outline a short-duration milling strategy to engineer powder-state attributes for improved sinterability.